1996
DOI: 10.1007/bf02599588
|View full text |Cite
|
Sign up to set email alerts
|

Lump detection is enhanced in silicone breast models simulating postmenopausal breast tissue

Abstract: We varied the softness and nodularity of silicone breast models to assess the effects of age-related breast tissue characteristics on lump detection. In two sets of six silicone breast models manufactured to simulate premenopausal and postmenopausal breast tissue, respectively, 82 internal medicine attending and housestaff physicians more readily detected lumps among models simulating older breast tissue. The proportion of models with one or more false-positive findings was higher among models simulating postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Overall, the 1.0‐cm hard lump was easiest to detect (94%) and the 0.3‐cm soft lump was the most difficult to detect (4%); none of the 80 physicians in the study detected the 0.3‐cm, soft, deeply placed lump. A more recent study, also using the MammaCare evaluation set of silicone breast models, reported that the sensitivity of detection decreased from 78% to 38% for 1.0‐cm versus 0.3‐cm lumps, from 61% to 52% for hard versus soft lumps, and from 63% to 53% for medium depth versus deep lumps 40 …”
Section: Tumor Patient and Examiner Characteristics That Influence mentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, the 1.0‐cm hard lump was easiest to detect (94%) and the 0.3‐cm soft lump was the most difficult to detect (4%); none of the 80 physicians in the study detected the 0.3‐cm, soft, deeply placed lump. A more recent study, also using the MammaCare evaluation set of silicone breast models, reported that the sensitivity of detection decreased from 78% to 38% for 1.0‐cm versus 0.3‐cm lumps, from 61% to 52% for hard versus soft lumps, and from 63% to 53% for medium depth versus deep lumps 40 …”
Section: Tumor Patient and Examiner Characteristics That Influence mentioning
confidence: 99%
“…The contribution of various palpation components to CBE effectiveness, including the extent of area examined, position of the breast tissue, type of finger motion, part of the finger, number of fingers, pressure, search pattern, and duration of search have been the focus of several investigations. Most of these studies have used silicone breast models to simulate the human breast; many have used the standardized research and evaluation set manufactured by the MammaCare Corporation, enhancing the degree of comparison that can be made across studies 38 , 40 . This research and evaluation set includes six silicone breast models containing 18 standardized lumps that vary in size (0.3, 0.5, or 1.0 cm), hardness (20, 40, or 60 durometers, with 60 being the hardest), and depth of placement (medium or deep).…”
Section: The Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, simulated lumps as small as 3.0 mm diameter were detectable when embedded in breast-like materials (which is an order of magnitude more pliant than prostate tissue) [910]. Aside from the lump size findings, abnormality depth and hardness appear to have a minimal impact, whereas the stiffness of surrounding tissue may decrease one's ability to detect deeper lumps [11]. …”
Section: Introductionmentioning
confidence: 99%